Studi Keselamatan Dan Keamanan Transportasi Diperlintasan Sebidang Antara Jalan Rel Dengan Jalan Raya: (Studi Kasus Perlintasan Kereta Api di Jalan Cicalengka-Majalaya) - Aditya, Septian; Saepudin, Uu; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
The intersection between highways and railway tracks is a traffic conflict point that has the potential to cause accidents. One such intersection is at the level crossing on Cicalengka-Majalaya Road in Kabupaten Bandung, which serves as a meeting point between two modes of transportation with different traffic flows. This condition can lead to problems such as accidents or traffic flow obstructions. This study aims to analyze the level of safety and security at the railway crossing on Cicalengka–Majalaya Road, Kabupaten Bandung. The method used is a quantitative approach with direct surveys through observation of facilities, crossing conditions, traffic volume, and road user behavior, as well as secondary data in the form of train schedules from relevant agencies. All data were analyzed statistically to provide an objective overview of the safety and security conditions of the at-grade crossing. The research results indicate that the Cicalengka–Majalaya level crossing is considered high-risk because, although the road level of service (LOS) is in the stable category B and the peak hour traffic volume (5796–6433 smpk) still meets safety standards (12,500–35,000 smpk), this crossing does not comply with the technical standards of the Directorate General of Land Transportation, with only 31% of required facilities provided, and the sight distances for road users (28 m compared to the 150 m standard) and train drivers (231 m compared to the 500 m standard) not meeting requirements, thus necessitating improvements in safety facilities and sight distances.